Pengembangan Petunjuk Praktikum Pendidikan berbasis Salingtemas - Dwiyani Anjar Martitik (Yayasan Azhar Amanaa Yogyakarta, 2023)
Animal systematics is one course, it used to be animal taxonomy. The scope of animal systematics material is wider, while animal taxonomy is just the part of it. There is a way to increase undergraduate students understanding about the material is with practical activities. The aim of this study is to develop Science, Environment, Technology and Society (SETS)-Based Animal Systematics Practicum Module. There were four steps, the first one was practicum module framework development; the second one was matching up the practicum module with the framework; the third step was practicum module review and improvement; the last step was praticum module implementation. The result from material and media expert were 84% and 88.89%. While student’s responses average was 88.2%. This data showed that this practicum guide is good enough to be implemented.